Toxicological Assay-Guided and Fabricated Feeding and Drinking Troughs for Intensive Deep-Litter Poultry Farming System - Adejo , Godwin Ojochogu; Adejo, Evelyn UnekwuOjo; Eleanya, Kelechi; Adejo, Sunday UnenwOjo (International Journal of Poultry Science, 2019)
Background and Objective: Main stream contemporary approach to controlling the impacts of diseases among poultry birds rely largely on curative measures through administration of drugs to infected birds. Most times, as observed in the deep litter poultry farming system, entire flocks including uninfected birds receive treatments they do not need. As such, unguarded use of chemical drugs/antibiotics has led to wastages and accumulation of chemical residues in poultry products with associated health hazards to human consumers. However, wanton and frequent drug usage in poultry is avoidable if feeding and drinking equipment are designed to curb transmission of infection among birds. Materials and Methods: Using toxicological assays as guide and with efficiency and simplicity in view, two newly field-tested and recently patented equipments called ‘healthy liquid drinking trough (HDT)’ and ‘healthy feeding trough (HFT)’ that systematically exclude contamination of the feeding and drinking channels, thereby, eliminating wide-spread infection and transmission of diseases in the (intensive) deep litter poultry farming system were designed. Results: Upon combined usage, they automatically and drastically reduced both the amount and frequency of antibiotics use in poultry by >50%. Additionally, they conferred optimization of feed and water utilization/elimination of wastage by >80%, reduced labour by >70%, reduced production cost by about 15% and reduced chemical residues in poultry meat or eggs by >85%. Conclusion: These new technologies are cheap and they require minimal energy input. They are likely to improve safety of poultry products for consumers’ health, increase marketability locally and for export. In addition, they can increase output and profit especially among poultry farmers and poor families in developing countries who keep poultry or inevitably utilize poultry products.